Clinical significance of hemostasiological screening for thrombophilia in pregnant women with former thrombosis - J. Kh. Khizroeva; N. N. Babaeva; N. A. Makatsariya; I. Elalamy; J-C. Gris (Акушерство, гинекология и репродукция)
Introduction. Pregnancy management in post-thrombotic women is challenging, because women with previous episode of venous thromboembolic complications (VTEC) have a 3–4 times higher risk of its exacerbation during than outside of subsequent pregnancies.Aim: to improve effective prenatal counseling program for women with former venous thrombosis and ischemic stroke to prevent recurrence of arterial and venous complications as well as pregnancy outcomes for mother and fetus.Materials and Methods. A single-center observational study was conducted involving 50 patients with arterial and venous thrombosis and pregnancy complications in anamnesis and 40 patients with a physiological course of pregnancy. To improve existing methods of thrombosis prevention, risk factors such as gene polymorphisms for plasminogen activator inhibitor-1 (PAI-1), coagulation factor II (prothrombin; F2: Thr165Met), coagulation factor I (fibrinogen; FGB I/D) were investigated as potential new candidates of thrombosis risk markers in pregnant women and puerperas.Results. In 24 (48 %) of 50 women with former arterial and venous thrombosis and pregnancy complications, were found to develop thromboembolic complications during pregnancy. Risk assessment performed according to the existing thrombosis risk scales, revealed that only 7 (29.2 %) patients were considered as candidates for thromboprophylaxis and received anticoagulant therapy. The remaining 17 women who subsequently developed thrombosis received no anticoagulant therapy. Unfortunately, most women were not tested for thrombophilia despite a history of pregnancy complications (fetal loss, preeclampsia, fetal growth retardation). The hereditary thrombophilia of high thrombogenic risk occurred in 5 (20.8 %) of 24 women with thrombosis during pregnancy (3 – homozygous forms of factor V Leiden mutation, 1 – reduced protein C and 1 – deficiency of protein S and antithrombin). Circulation of various types of antiphospholipid antibodies was found in 13 (54.2 %) of 24 women. Homozygous polymorphisms of the PAI-1 4G/4G (45.8 %) and prothrombin F2 Thr165Met (20.8 %) genes were significantly more common in women with former thrombosis and obstetric complications compared with the control group (p < 0.001 and p = 0.023, respectively; odds ratio = 6.744; 95 % confidence interval = 1.195–38.056).Conclusion. In all cases examined, 24 women with thrombosis during pregnancy revealed to suffer from hereditary or acquired thrombophilia of high thrombogenic risk. After exclusion of high-risk thrombophilia, a number of gene polymorphisms exist that may be new candidates as a risk factor for thrombosis in pregnant women. More than 50 % of thrombosis cases in our study were associated with the homozygous genotype PAI-1 4G/4G (p < 0.001) and F2 Thr165Met (p < 0.001).